Stroke thrombolysis complicated by ST elevation myocardial infarction (STEMI). (5th March 2018) - Flower, Mark; Harvey, James; Hunter, Jonathan
Abstract : An 84-year-old male Jehovah's Witness presented to the emergency department 1 hour after onset of left facial droop and left upper limb weakness. Thrombolytic stroke treatment was commenced as per local thrombolytic protocol with intravenous recombinant tissue plasminogen activator (rtPA) at 2 hours and 25 min following onset of symptoms. Almost immediately after rtPA infusion the patient reported chest pain and had ECG changes consistent with a diagnosis of anterior ST elevation myocardial infarction. At angiogram, a graft study showed severe native coronary artery disease. The left internal mammary artery graft was patent to the left anterior descending artery (LAD); however, the apical LAD was occluded, with the appearance suggestive of embolic occlusion.